1967
DOI: 10.1139/b67-106
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition of Brussels Sprout Leaf Senescence by Kinins

Abstract: The senescence of leaf discs cut from mature B r~~s s e l s s p r o~~t leaves is retarded by a number of kinins. Other plant growth reg~~lators are without effect. When young expanding leaves are treated with Itinins the senescence processes appear to be accelerated. The ef-lect of N-6-benzyladenine on the structure of the cell organelles in young and old leaves has bee11 studied by electron microscopy. I t has been found that ill mature leaves the chloroplast is the organelle which senesces first and the brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

1968
1968
1980
1980

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Within only a few exceptions, the loss of protein from the discs was no greater than the loss from the attached leaves. (2,3,5,14), although bean leaf discs lose little protein and only 20% chlorophyll (7,15).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Within only a few exceptions, the loss of protein from the discs was no greater than the loss from the attached leaves. (2,3,5,14), although bean leaf discs lose little protein and only 20% chlorophyll (7,15).…”
Section: Methodsmentioning
confidence: 99%
“…Some workers have reported differences in the senescence pattern of attached leaves compared to leaf discs (10,11,13,16,18,19). Dennis et al (5) found different changes in the chloroplast ultrastructure during senescence of attached old leaves and detached aged leaves. Lewington et al (11) con-cluded that senescence of detached leaves was not the same process as senescence of attached leaves.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Radioactive spots were eluted with 2 ml of 20(% ethanol, and 0.1 ml was estimated. Spots 6 Table IV. Effect of Kilietint onl "CO2 Ilicorporationt info PIhosphate-Esters Fifty leaf discs (9-mm diameter) pretreated for 24 hr with kinetin (5 ,g/ml) were exposed to "CO2 for 1.5 hr.…”
Section: Effects Of Plant Growth Hormones On Starch Content Of Leaf Dmentioning
confidence: 99%